2007
DOI: 10.1590/s0103-97332007000200004
|View full text |Cite
|
Sign up to set email alerts
|

From confining fields on the lattice to higher dimensions in the continuum

Abstract: We discuss the relation between lattice phenomenology of confining fields in the vacuum state of Yang-Mills theories (mostly SU(2) case) and continuum theories. In the continuum, understanding of the confinement is most straightforward in the dual formulation which involves higher dimensions. We try to bridge these two approaches to the confinement, let it be on a rudimentary level. We review lattice data on low-dimensional vacuum defects, like monopoles, center vortices. There is certain resemblance to dual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 81 publications
0
32
0
Order By: Relevance
“…As we have emphasized above, very similar problems are met when studying center dominance in the maximal center gauge (MCG) [22][23][24][25] and some possible interpretations have been discussed [24,26]. One should also study how the problem is related to the choice of a particular starting point on the gauge orbit (belonging to Landau gauge in our case) and perform more extensive studies in which the global maximum of the MAG functional is searched for via better algorithms, like for instance simulated annealing [27].…”
Section: Gauge Dependencementioning
confidence: 91%
“…As we have emphasized above, very similar problems are met when studying center dominance in the maximal center gauge (MCG) [22][23][24][25] and some possible interpretations have been discussed [24,26]. One should also study how the problem is related to the choice of a particular starting point on the gauge orbit (belonging to Landau gauge in our case) and perform more extensive studies in which the global maximum of the MAG functional is searched for via better algorithms, like for instance simulated annealing [27].…”
Section: Gauge Dependencementioning
confidence: 91%
“…In order to describe condensation one should use the concepts of Euclidean interacting quantum field theory instead of random walks which describe the states of only one particle. Condensate then corresponds to nonzero background field, as in the Higgs model (for a related discussion see, e.g, [22,23]). It is not clear whether this picture remains valid for the theory of random surfaces, because required nonperturbative apparatus of string field theory is almost not developed.…”
Section: Discussionmentioning
confidence: 99%
“…Quadratic divergence in the effective action (1) corresponds to vacuum oscillations of these two-dimensional fields [22,23]. Localization on center vortices was also directly observed in lattice simulations -for instance, it was found that in the maximal Abelian gauge almost all trajectories of Abelian monopoles belong to center vortices [20].…”
Section: Fields Localized On Center Vorticesmentioning
confidence: 90%
See 2 more Smart Citations